Current distribution and status of the Eurasian otter Lutra lutra in South Korea. Issue 5 (18th September 2020) - Jo, Yeong-Seok; Lee, Oh-Sun; Park, Tae-Jin; Kim, Han-Na; Baccus, John T.
Abstract: The status of Asian populations of the Eurasian otter Lutra lutra is largely unknown. Since its designation as a Natural Monument (in 1983) and as Endangered (in 1997) in South Korea the authorities there have been trying to conserve and recover the species. We conducted a national otter survey by standard methods in 2017 and compared the current otter distribution to those recorded in a previous survey (2010). We found otter signs in 84.5% of 1, 105 10 × 10 km grid cells, with the highest sprainting intensity in the south-west in the Yeongsan River Basin and on the south coast, where we recorded 7.05 and 6.26 spraints/site, respectively. Despite relatively low spraint densities, the otter has expanded its range since 2010 by colonizing urban areas. This trend suggests that South Korea could be a source area for the recovery of the Eurasian otter in East Asia.